Cities Without Slums (Kotaku) Program in the Perspective of Community Empowerment in Kampung Tua Tanjung Riau Batam - Albert RR Palit; Renggi E Siregar; Yuanita FD Sidabutar (Budapest International Research and Critics University, 2022)
Urban slums arise due to the inability or failure of the community to be able to compete to reach and have all the needs to support their needs. The Kotaku program is carried out as an effort to strengthen elements of universal accessibility, resilience to disaster risk, and/or environmental sustainability, especially with regard to drinking water and/or sanitation consisting of solid waste, domestic wastewater, and drainage by facilitating pilot locations. become a learning model to be adopted, adapted, and replicated by local governments in other locations. The Kotaku program intends to build an integrated system for slum management, where local governments lead and collaborate with stakeholders in planning and implementation, and promote community participation. Empowerment is an important aspect in the development of the Kotaku Program. This is because village development takes a lot of resources owned by the community. The community has an important role to support the success of the development of tourist villages so that people who are powerless need to be empowered to create independence and economic prosperity for the community. This research method is qualitative research using data collection techniques, namely interviews and documentation and literature study. Interview is one method of collecting data with data sources either directly or indirectly. From the research results, it was found that the Kotaku program has many empowerment opportunities for the community, with income opportunities for the community and reducing unemployment as well as making the latest creations and being able to open their own jobs. With the Kotaku program, Tanjung Riau can become a place that supports improving the environmental image for the city of Batam.